Herbicide atrazine alters the microbiota of the filamentous green alga cladophora sp. cultured from Thailand - Anchittha Satjarak,; Jittra Piapukiew,; Wikrom Chanthapatchot,; Karnjana Ruen-Pham,; Alisa S. Vangnai, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The attached green alga Cladophora known to harbor microbiota that play important roles in ecosystem, is one of the most common freshwater filamentous green algae in rivers globally, including those in the northern part of Thailand. These rivers mostly run through agricultural regions where herbicides are heavily used to improve crop quality and quantity. The extensively-used herbicide atrazine persists in soil sediments through transport by surface runoff to rivers. The effect of such herbicide contamination on Cladophora microbiota in Thailand have not been investigated. To acquire this information, 16S rDNA amplicons were used to compare microbiota of Cladophora sp. cultures treated with a spectrum of atrazine concentrations. The results showed that the Cladophora microbiome included at least 106 possible Operational taxonomic units (OTUs) representing twelve bacterial phyla which are Acidobacteria, Actinobacteria, Armatimonadetes, Chloroflexi, Cyanobacteria, Deinococcus-Thermus, Epsilonbacteraeota, Nitrospirae, Patescibacteria, Planctomycetes, Proteobacteria, and WPS-2, representing both core and local algal bacteria. The presence of atrazine was also correlated with changes in richness of bacterial taxa suggesting that these algal epibiotic bacteria were differently affected by atrazine treatments.